Effect of Mycotoxins on Reproduction and Milk Quality of Dairy Cattle and its Amelioration by Natural Adaptogen “Betulin” - Larisa Gnezdilova; Sergey Fedotov; Zhora Muradyan; Serafim Rozinsky; Regan Reddy Gade (Qubahan Academic Journal)
The purpose of this study was to ascertain the effect of mycotoxins on the reproduction and milk quality and its amelioration by “Betulin” in lactating Holsteinized Russian Black Pied cows divided into 2 complexes which were further split into 2 groups. On general clinical examination of the reproductive tract, it was observed that the high milk yielding cows have low rates (82.14 ± 1.59%) of productive offspring in the extensive method, while it was higher (85.12 ± 2.31%) in the intensive method of rearing. During the experiment, mycotoxin contamination was observed in the feed, especially for Zearalenone (ZEN), the concentration of which was 9.5% in corn silage and 8.9% in concentrate feed. In cows, the presence of ZEN or Fusarium toxin contributed significantly to infertility and decreased milk production (8523.9±112.5 vs 7153.8±99.7 kg). However, lactating cows showed tolerance to mycotoxins, as evidenced by insignificant changes in the indicators of milk quality in subject animals. Further, the use of the natural adaptogen “Betulin” added to an increase in milk yield and an improvement in the quality and sanitary parameters of milk.